2021
DOI: 10.1016/j.jid.2020.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α3β1 on Tumor Keratinocytes Is Essential to Maintain Tumor Growth and Promotes a Tumor-Supportive Keratinocyte Secretome

Abstract: The development of integrin-targeted cancer therapies is hindered by incomplete understanding of integrin function in tumor cells and the tumor microenvironment. Previous studies showed that mice with epidermisspecific deletion of the a3 integrin subunit fail to form skin tumors during two-step chemical tumorigenesis, indicating a protumorigenic role for integrin a3b1. Here, we generated mice with tamoxifen-inducible, epidermis-specific a3 knockout to determine the role of a3b1 in the maintenance of establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Cadherins and integrins are two major families of adhesion molecules involved in essential cellular processes such as adhesion and proliferation [ 65 , 66 ]. In particular, integrins play a relevant role in the regulation of keratinocytes and endothelial cell survival and proliferation [ 67 , 68 ]. Moreover, our analysis demonstrated that BMSC-EVs contained proteins associated to metabolomic processes such as fructose galactose metabolism and glycolysis [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins and integrins are two major families of adhesion molecules involved in essential cellular processes such as adhesion and proliferation [ 65 , 66 ]. In particular, integrins play a relevant role in the regulation of keratinocytes and endothelial cell survival and proliferation [ 67 , 68 ]. Moreover, our analysis demonstrated that BMSC-EVs contained proteins associated to metabolomic processes such as fructose galactose metabolism and glycolysis [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have linked certain α3β1 functions to TGF-β signaling, as reviewed [ 54 ], suggesting possible co-involvement of α3β1 and TGF-β in the repression of RELN expression. Moreover, we recently showed that α3β1 regulates the secretion by tumor keratinocytes of not only ECM proteins and extracellular proteases, but also of some growth factors and cytokines [ 59 ], leaving open the possibility that integrin crosstalk with other growth factor/cytokine receptors may regulate Reelin expression or function.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, topical treatment with the tumor initiator 7,12-dimethylbenz[ a ]-anthracene followed by repeated treatment over weeks with the tumor promoter 12- O -tetradecanoylphorbol-13-acetate induces benign skin tumors (i.e., papillomas), a proportion of which progress to squamous cell carcinoma (SCC) depending on the genetic background ( Abel et al., 2009 ). Previous studies by our group and others have used this model to demonstrate that epidermal α3β1 is essential for skin tumor formation ( Longmate et al., 2017 ; Sachs et al., 2012 ) and that it is also required for the maintenance of skin tumor growth ( Longmate et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the important roles for epidermal α3β1 in the regulation of the keratinocyte (KC) secretome ( He et al., 2018 ; Longmate et al., 2021 ; Ramovs et al., 2020 ) and in cross-talk to stromal cells within the tumor microenvironment (TME) ( Longmate et al., 2021 ; Ramovs et al., 2020 ; Zheng et al., 2019 ). Extracellular proteases are major constituents of the secretome that contribute to the state of the ECM by mediating matrix degradation and remodeling ( Bonnans et al., 2014 ), which is accomplished by altering ECM constituents and biophysical properties ( Niland and Eble, 2020 ).…”
Section: Introductionmentioning
confidence: 99%